Immunomodulatory Effects of Robinia pseudoacacia Polysaccharides on Live Vaccine against Infectious Bronchitis in Immunosuppressive Chickens - Qiuyan Sun; Fang Li; Caixia Wang; Meiyan Shen (International Journal of Polymer Science)
In order to investigate the immunomodulatory effect of Robinia pseudoacacia Polysaccharides (RPPS) on vaccine against Infectious Bronchitis (IB) in immunosuppressive chickens, the artificial leukemia chicken model was established and then the IB live vaccine (H120 strain) was immunized. The immunomodulatory efficacy of RPPS was determined by the antibody titer, the lymphocyte transformation rate in peripheral blood, the CD4+ and CD8+ T lymphocyte levels in peripheral blood, and the cytokine levels in the serum. The results showed that RPPS could not only enhance the immune effect of IB live vaccine but also improve the immunity of immunosuppressive chickens. Thus, the function of RPPS immunopotentiator could be further developed.